STRATEGI TRAX FM SEMARANG DALAM MEMPERTAHANKAN BRAND ENGAGEMENT DIKALANGAN PENDENGARNYA - Sarah Indah Putri; Turnomo Rahardjo (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2021)
Radio is already in danger of dying out due to its disability to keep up with digitalization. In 2019, radio penetration is decreased from 37.6 percent to 34.3 percent in Semarang. People today are tend to use digital devices and leave radio to fulfil their needs. This change resulted in decreased public interest in listening to radio. However, in the midst of the decline in radio's existence, there are still radios that are actively broadcasting and still exist among their listeners, one of it is Trax FM Semarang which has a good brand engagement and maintains its existence among listeners. This study aims to determine the Trax FM Semarang strategy in maintaining brand engagement among listeners. This research refers to the interpretive paradigm with a single case study method. The data collection technique used was in-depth interviews and collecting research results in document form. This study uses Customer Relationship Management Theory. This study also uses the concept of Radio Broadcasting Programming and Brand Engagement. The results of this study explain that the strategies used by Trax FM Semarang in maintaining its brand engagement include always making broadcasting programs that are appropriate and “connecting” with its target market. In keeping up with technological developments, Trax FM Semarang is always active in creating content on its social media, developing radio access on streaming websites and mobile applications. For relations with external stakeholders, Trax FM Semarang always maintains good relationships and also moves to become an Event Organizer according to client needs and for Trax FM's own needs.